Pelatihan Pembuatan Deterjen Cair Dengan Mesin Kapasitas 100 Liter Untuk Meningkatkan Produktivitas Usaha Laundry Di Deli Serdang - Nurjamiyah; Muhammad Arifin; Zaharuddin (Forum Kerjasama Pendidikan Tinggi, 2024)
Deli Serdang is a regency located in North Sumatra Province. Where one of the villages in Deli Serdang district is Tembung village. Judging from the resources available in Deli Serdang, especially Tembung Village has resources that have good potential to develop businesses. One of the businesses in Tembung Village is a laundry service business that was started in 2020. Based on the results of the survey that has been carried out, the proposer determines the laundry business group owned by Mr. Sugeng and his wife as a partner. The proposer and partners agreed on several problems that have been faced by partners, including that in the production process, making liquid detergent is still done manually (stirring without tools) so that the production results cannot be thick, the texture of liquid detergent is watery and the production capacity is not large. In addition, the process of making liquid detergent takes a long time to dissolve all the raw materials. In addition, the liquid detergent concoction is only used for the laundry business. However, the business owner wants to market his liquid detergent concoction to the wider community in order to get additional income. This has not been possible because the distribution license of the liquid detergent product does not yet exist. The purpose of this PKM activity is to provide socialization, training and mentoring to partners regarding: 1) making liquid detergent using machine tools, which was previously done manually; 2) making marketing applications and helping with product distribution licenses. The method of service implementation is to provide socialization, training and mentoring to Karomah Laundry partners. The targeted results in this Community-Based Empowerment Program are the increased efficiency of the liquid detergent production process with the existence of a more modern liquid detergent making equipment in the partner industry so that it can increase the economy of laundry entrepreneurs. More effective product marketing methods, by making product marketing applications and training on the use of applications as a tool in marketing products that are more clearly effective and efficient. With the issuance of a distribution permit for the liquid detergent product, the partner can officially market the product to the wider community. The results of the community service also showed that most participants were interested in making their own liquid detergent products so that it could be an opportunity for them to get additional income from making liquid detergent. Participants also felt satisfied with the activity. Because this can be related to developing participants' interests and talents in making liquid detergent. In the future, this activity will still be held as a continued form of community service activities.